Pro Power BI Desktop : self-service analytics and data visualization for the power user - Aspin, Adam (Apress, 2020)
Deliver eye-catching and insightful business intelligence with Microsoft Power BI Desktop. This new edition has been updated to cover all the latest features of Microsofts continually evolving visualization product. New in this edition is help with storytelling--adapted to PCs, tablets, and smartphones--and the building of a data narrative. You will find coverage of templates and JSON style sheets, data model annotations, and the use of composite data sources. Also provided is an introduction to incorporating Python visuals and the much awaited Decomposition Tree visual. Pro Power BI Desktop shows you how to use source data to produce stunning dashboards and compelling reports that you mold into a data narrative to seize your audiences attention. Slice and dice the data with remarkable ease and then add metrics and KPIs to project the insights that create your competitive advantage. Convert raw data into clear, accurate, and interactive information with Microsofts free self-service BI tool. This book shows you how to choose from a wide range of built-in and third-party visualization types so that your message is always enhanced. You will be able to deliver those results on PCs, tablets, and smartphones, as well as share results via the cloud. The book helps you save time by preparing the underlying data correctly without needing an IT department to prepare it for you. You will: Deliver attention-grabbing information, turning data into insight Find new insights as you chop and tweak your data as never before Build a data narrative through interactive reports with drill-through and cross-page slicing Mash up data from multiple sources into a cleansed and coherent data model Build interdependent charts, maps, and tables to deliver visually stunning information Create dashboards that help in monitoring key performance indicators of your business Adapt delivery to mobile devices such as phones and tablets.